Employing an 'employer-led' design? : An evaluation of the development of Diplomas - Ertl, Hubert [Verfasser]; Stasz, Cathleen [Verfasser] (My University, 2010)
"This paper presents some of the findings of an evaluation of the development of the first fourteen 14-19 Diplomas in England. It focuses on the question whether the government's aim to develop the new qualifications in an employer-led way has been fulfilled. In order to answer this question, the paper evaluates the contributions of employers in the Diploma development process, the strategies used to engage employers and employers' satisfaction with the outcome. The paper concludes that while employers have had a significant role in defining the content of Diplomas, they have been by no means leading or driving the overall process of qualification making. Due to the complex nature of the qualification system and the need for collaboration of a variety of actors, the role of employers may more accurately be described as key partners in the development process." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; L 1.3 Curriculumentwicklung; G 1.2.3.2 Anforderungen & Bedarfe; S 3.5.4 Sozialpartner; I 2.2.1 Westeuropa; Berufsbildung; Hochschulbildung; Berufliche Qualifikation; Curriculumentwicklung; Qualifikationsentwicklung; Qualifikationsanforderung; Arbeitgeber; England